2020
DOI: 10.1155/2020/4298509
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Inactivation of Trigger Points Combined with Muscle Fascia Stripping by Liquid Knife in Treatment of Postherpetic Neuralgia Complicated with Abdominal Myofascial Pain Syndrome: A Prospective and Controlled Clinical Study

Abstract: Objective. To evaluate ultrasound-guided inactivation of myofascial trigger points (MTrPs) combined with abdominal muscle fascia stripping by liquid knife in the treatment of postherpetic neuralgia (PHN) complicated with abdominal myofascial pain syndrome (AMPS). Methods. From January 2015 to July 2018, non-head-and-neck PHN patients in the Pain Department, The First Affiliated Hospital of Soochow University, were treated with routine oral drugs and weekly paraspinal nerve block for two weeks. Patients with 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Concerning other diseases, the diagnostic contribution of US was even assessed in sciatica, where it showed morphological changes of the nerve, with enlargement and higher stiffness in the impaired nerve [ 27 , 28 ]. In the cases of herpes/postherpetic neuralgia, US was mainly used to guide the treatment, improving painful symptoms [ 29 ]. Patients with chronic pain were successfully treated with US-guided block [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning other diseases, the diagnostic contribution of US was even assessed in sciatica, where it showed morphological changes of the nerve, with enlargement and higher stiffness in the impaired nerve [ 27 , 28 ]. In the cases of herpes/postherpetic neuralgia, US was mainly used to guide the treatment, improving painful symptoms [ 29 ]. Patients with chronic pain were successfully treated with US-guided block [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conventional treatment has an ideal therapeutic effect on PHN patients without MPS, but the therapeutic effect on PHN patients with MPS is not clear. Unfortunately, some studies have shown that more than a half of PHN patients had MPS [ 8 ]. This study showed that for these patients, DN treatment on PHN mixed with MPS had an unexpected good effectiveness, the effective rate was as high as 92.9%, and the recurrent rate was as low as 7.1% in the follow-up study three months later after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dry needling (DN) treatment is a safe technique, which leaves no side effects other than a slight discomfort that disappears after 3 days at the most [ 7 ]. Some research found out that more than a half of PHN patients had mild to moderate pain mixed with MPS [ 8 ]. MPS is also found in other conditions, such as osteoarthritis of the knee [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen-ozone injection: Oxygen-ozone injection induces muscle twitching in the same way as stimulating MTrPs by a tiny needle producing a therapeutic effect similar to dry-needle treatment. Compared to corticosteroid injection, ozone can be metabolized and transformed into oxygen with the final absorption into the tissue, avoiding the side effect of local adhesion and the systematic response of a corticosteroid[ 52 ]. The concentration of ozone injected should be no more than 30 μg/mL, with the dose of 1 mL to 5 mL for a single trigger point and a maximum of 30 mL at a time.…”
Section: Therapeutic Principles and Methodsmentioning
confidence: 99%